A systematic review of the factors associated with athlete burnout in team sports - Woods, S.; Dunne, S.; Gallagher, P.; McNicholl, A. (International Review of Sport and Exercise Psychology, 2025)
Athlete burnout is a psychological syndrome with substantial negative consequences, including depression and sport dropout. It has been linked to a range of factors, some of which may vary across different sport-types. This review is the first to synthesise variables examined in relation to burnout in team-sports specifically. An online search of seven relevant databases yielded 59 papers examining 123 burnout correlates. Eligible papers were peer-reviewed, quantitative empirical studies, which assessed burnout using the Athlete Burnout Questionnaire. Results are reported in-line with PRISMA guidelines. Weighted meta-analysis (WMA) assessed the strength of the relationship between burnout dimensions and 18 variables examined across =3 samples. A narrative synthesis of the remaining cross-sectional, longitudinal and mediating/moderating relationships provides a comprehensive overview of the literature. Burnout displayed a negative relationship with autonomy, competence, relatedness, self-determined motivation, positive affect, autonomy supportive coach, harmonious passion, self-oriented perfectionism and social support, and a positive relationship with amotivation, negative affect, obsessive passion, socially-prescribed perfectionism, ego-involving climate, playing experience and controlling coach style in the WMA. Some variability in relationships was identified across the dimensions of burnout. The results highlight the key factors associated with the dimension of burnout in team sports, which may inform targeted intervention strategies.